Why do nestling birds fledge early in the day?. (April 2021) - Santema, Peter; Schlicht, Lotte; Beck, Kristina B.; Sheldon, Ben C.; Kempenaers, Bart
Abstract : In altricial birds, leaving the nest is a key life history transition associated with a high risk of mortality. Studies of numerous species have shown that young typically fledge early in the day, and it is often asserted that early fledging is important for survival; however, evidence for this hypothesis is limited. We used an automated monitoring system to obtain precise fledging times of 1582 young blue tits, Cyanistes caeruleus, from 230 nests. As expected, nestlings primarily fledged early in the day (84% fledged before midday). However, we found no evidence that early fledging was associated with higher postfledging survival (i.e. recorded the following autumn or later). We propose two alternative explanations for the morning peak in fledging. Hypothesis 1 is that some offspring reach a developmental threshold for fledging overnight and leave the nest early the next day. This is supported by our observation that offspring that fledged early in the day tended to be more developed than those that fledged later in the day, that is, they were older and had a high body mass (measured at 14 days of age) for their fledging age. Hypothesis 2 is that the timing of fledging is related to parental provisioning behaviour. Our results do not support this hypothesis. Parents reduced their nest visit rate over the course of the day, but offspring did not fledge earlier when their parents decreased their visit rate more strongly with time of day. In conclusion, our results do not support the notion that the time of fledging affects survival but suggest a link with nestling development. Highlights: In altricial birds, nestlings typically fledge early in the day. This is often assumed to improve survival, but with little supporting evidence. We monitored the precise fledging times of 1582 blue tits from 230 nests. Fledging time was not associated with the probability of local survival. Instead, fledging time was related to the developmental stage of nestlings.